Kewenangan Presiden dalam Reshuffle Kabinet di Indonesia (Tinjauan Siyasah Dusturiyah) - Mahdalena Nasrun; Nurul Fithria; Abd Razak; Hasanuddin Yusuf Adan; Ratul Via Ramadhan (Kartika: Jurnal Studi Keislaman, 2026)
The absence of specific regulations governing the procedures for changing the composition of the cabinet within the Indonesian national legal framework has given rise to debate among academics regarding the limits of the president's authority and its compatibility with the principles of siyasah dusturiyah. This study is directed at examining the juridical basis for the President's authority to carry out a cabinet reshuffle according to positive law, as well as assessing its implementation based on the values ​​of justice ('adl), trust, deliberation (syura), and benefit (maslahah mursalah). This research uses a normative juridical method with a conceptual approach, statutory regulations (statute approach), and a fiqh siyasah dusturiyah perspective. The findings show that the cabinet reshuffle carried out by Prabowo Subianto in 2025 is considered constitutionally valid because it is the president's prerogative, but in the siyasah dusturiyah review its implementation does not fully reflect these four principles. This is influenced by a lack of transparency, the absence of published performance indicators, the dominance of unilateral decision making, and the impact of policies that have not been analyzed comprehensively. As a result of this gap, the potential for achieving the president's vision and mission is hampered, bureaucratic stability is disrupted, and the cabinet's performance is not optimal as perceived by the public.